Prevalence and incidence of intraventricular conduction disturbances among Chinese adults: Results from the Kailuan study - Wang, Binhao; Wang, Zhao; Yang, Xiaolei; Han, Xu; Yang, Yiheng; Chu, Huimin; Wu, Shouling; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Epidemiological data on intraventricular conduction disturbances (IVCDs) are limited in the Chinese population. We aimed to investigate the prevalence and incidence of different types of IVCDs among Chinese adults. Methods: From June 2006 to October 2007, a total of 100,250 individuals from the Kailuan Study underwent electrocardiogram examinations. Follow-up visits were performed biennially. The prevalence and incidence of right bundle branch block (RBBB), incomplete RBBB (IRBBB), left bundle branch block (LBBB), incomplete LBBB, left anterior fascicular block (LAFB), left posterior fascicular block (LPFB) and nonspecific IVCD (NIVCD) were calculated. Their association with risk factors and cardiovascular diseases was also investigated. Results: The prevalence and incidence of all IVCDs were 3.19% and 1.70%, respectively. RBBB, IRBBB and LAFB were the IVCD types that had the highest prevalence and incidence. The prevalence (3.67% vs. 1.29%; P<0.001) and incidence (1.93% vs. 0.84%; P<0.001) of IVCDs were higher among males than among females. The prevalence and incidence of most IVCD types increased with age. IRBBB, LBBB and LAFB were significantly associated with hypertension. LBBB and NIVCD were associated with diabetes mellitus. In addition, LBBB and LAFB were related to prior myocardial infarction. Conclusions: IVCDs differ in prevalence and incidence according to sex and age group. They also show disparate associations with other cardiovascular comorbidities. These differences need to be considered in daily clinical practice.